Study of Photoionization of Solids—Resonance Ionization. Issue 5 (1985) - Verdun, F.; Muller, J. F.; Krier, G.
Abstract : Multiphoton ionization (MPI) mechanism in the solid state being still controversial we coupled a tunable laser to the LAMMA 500 microprobe to reinvestigate, using different UV irradiations, the ionization of some organic and organometallic solid compounds. Two polycyclic aromatic hydrocarbons (PAH) anthracene and pyrene and metallic derivatives of copper and cadmium were tested. Preliminary results are consistent with thermal desorption of neutral molecules as the first step followed by photoionization in the vapor phase. Thus the ionization mechanisms described for gases or vapors, and in particular some REMPI or RIS processes appear to apply to our experimental conditions.